Miscanthus x giganteus crop fields hide a genotype of the invasive M. sacchariflorus. (4th October 2019) - Perrier, A; Hardion, L; Rozan, A; Staentzel, C; Combroux, I
Summary: Despite their putative invasive potential, Miscanthus taxa have been increasingly viewed as promising crops for bioenergy production. Miscanthus  x  giganteus is cultivated worldwide due to its high productivity, and its non‐spreading growth limits its risk of invasion. However, the genetic uniformity of its unique cultivated clone has recently been questioned. We used morphometry, nuclear microsatellites, AFLP fingerprints and nrDNA ITS barcoding to assess Miscanthus genotypes cultivated in eastern France. As expected, the globally cultivated clone was the main morphotype and genotype of our samplings; however, we also identified a second genotype, assigned to M. sacchariflorus, in the sampled fields. Morphological differentiation partially overlaps genotypic assignation, probably due to disturbance at the crop edges. We also show that Miscanthus taxa are misidentified in commercial nurseries. Our study confirms previous reports of the occurrence of other accessions in fields of M . x  giganteus . These taxonomic confusions limit the certainty that a single clone of M . x  giganteus is cultivated. In this context, M . x  giganteus crop fields may actually promote the dispersal of invasive Miscanthus taxa.